Strategi Pemerintah Kota Madiun dalam Penyelenggaraan Pembangunan Kesejahteraan Sosial Masyarakat Perkotaan - Lina Alfiyani; Andika Rahayu Marga Trisnawati; Muh. Niam (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The implementation of social welfare development in accordance with the characteristics and capabilities of the Madiun City government is a strategic effort in improving the quality of life and welfare of the people of Madiun City. This study uses a qualitative research methodology, aiming to provide an overview of the various efforts implemented by the Madiun City government in implementing social welfare development for urban communities. The results of the study provide an overview of the perspective of the Madiun City government in implementing social welfare development based on the Human Development Index (HDI), with the direction of social development on equalizing the improvement of the quality of life of the people of Madiun City. The strategic steps of the Madiun City government are to maximize community and private participation and are integrated into social pillars that support social welfare development. The intervention of the Madiun City government by life cycle is a strategic effort by the government in overcoming problems and developing the capabilities of the people of Madiun City through programs based on the life stage of the people of Madiun City. Social services in Madiun City are manifested through various social security, social protection, and social empowerment programs that aim to prevent social risks and vulnerabilities, meet basic needs, and improve the quality of life of the people of Madiun City.